2019
DOI: 10.1002/cne.24711
|View full text |Cite
|
Sign up to set email alerts
|

Ferret brain possesses young interneuron collections equivalent to human postnatal migratory streams

Abstract: The human early postnatal brain contains late migratory streams of immature interneurons that are directed to cortex and other focal brain regions. However, such migration is not observed in rodent brain, and whether other small animal models capture this aspect of human brain development is unclear. Here, we investigated whether the gyrencephalic ferret cortex possesses human‐equivalent postnatal streams of doublecortin positive (DCX+) young neurons. We mapped DCX+ cells in the brains of ferrets at P20 (analo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 36 publications
1
15
1
Order By: Relevance
“…4). Interestingly, arch-like organization is also observed in ferrets, which possess a gyrified cortex (Ellis JK et al 2019), suggesting that the presence of an arch is associated with cortical gyrification rather than evolutionary similarity with humans.…”
Section: Discussionmentioning
confidence: 97%
“…4). Interestingly, arch-like organization is also observed in ferrets, which possess a gyrified cortex (Ellis JK et al 2019), suggesting that the presence of an arch is associated with cortical gyrification rather than evolutionary similarity with humans.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, restructuring of the extracellular matrix by MMP2 promotes neuroblast migration (Hanics et al, 2017 ). Recent research has shown that in the early postnatal forebrain, nearby to the RMS, lies a dorsal migratory stream that supplies GABAergic neurons to late-developing prefrontal cortical areas in both humans (up to 5 months postnatally; Sanai et al, 2011 ; Paredes et al, 2016 ) and ferret (up to 90 days postnatally; Ellis et al, 2019 ). A large proportion of these interneurons express SCGN (Raju et al, 2018 ; Ellis et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Gasoni et al used an updated 3DISCO method to provide a quantitative analysis of gonadotropin-releasing hormone (GnRH) neuron origins, differentiation, migration, and their distribution 3D atlas in the fetal brain, revealing that GnRH positive neuron cells have potential roles in non-reproductive function (Figure 5 B) 90 . Additionally, the migration flow of immature neurons can also be studied in the early postnatal brain of some small animal models, which corresponds to the early development of human brains in this aspect (Figure 5 C) 91 , 92 . Furthermore, other biological stages that occur during neurodevelopment, including axonal guidance, synapse formation, and neuronal death, still need to be further studied through improved clearance techniques, leading to a comprehensive understanding of mammalian brain development.…”
Section: Development Of Brainmentioning
confidence: 99%